International employee perspectives on disability management. Issue 9 (24th April 2018) - Wagner, Shannon; Buys, Nicholas; Yu, Ignatius; Geisen, Thomas; Harder, Henry; Randall, Christine; Fraess-Phillips, Alex; Hassler, Benedikt; Scott, Liz; Lo, Karen; Tang, Dan; Howe, Caroline
Abstract: Purpose: To provide an international analysis of employees' views of the influence of disability management (DM) on the workplace. Methodology: An international research team with representation from Australia, Canada, China, and Switzerland collected survey data from employees in public and private companies in their respective regions. Due to lack of availability of current measures, a research team-created survey was used and a total of 1201 respondents were collected across the four countries. Analysis: Multiple linear (enter) regression was also employed to predict DM's influence on job satisfaction, physical health, mental health, workplace morale and reduced sickness absence, from respondents' perceptions of whether their company provided disability prevention, stay-at-work, and return-to-work initiatives within their organization. One-way ANOVA comparisons were used to examine differences on demographic variables including company status (public versus private), union status (union versus nonunion), and gender. Results: The perceived influence of DM programs was related to perceptions of job satisfaction; whereas, relationships with mental health, physical health, morale, and sickness absence were variable according to type of DM program and whether the response was related to self or others. Difference analyses (ANOVA) revealed significantly more positive perceptions for private and nonunion organizations; no gender effects were found. Conclusions: There is perceived value of DM from the perspective of employees, especially with respect to its value for coworkers. Implications for Rehabilitation: Rehabilitation efforts should continue to focus attention on the value of disability management (DM). In particular, DM that is fully committed to the biopsychosocial model would be supported by this research. Employees reported the most value in the psychosocial variables addressed by DM, such that rehabilitation professionals could focus on these valued aspects to improve buy-in from employees. The interest in coworker value may provide another avenue for rehabilitation efforts to increase uptake, by highlighting the value of intervention efforts for employee coworkers. Rehabilitation professionals in union environments may need to be particularly cognizant of the need for encouraging psychosocial and coworker value potentially seen by employees in order to increase acceptance and participation for organizational DM efforts.